2020
DOI: 10.1088/1361-648x/ab7f02
|View full text |Cite
|
Sign up to set email alerts
|

The high-pressure, high-temperature phase diagram of cerium

Abstract: We present an experimental study of the high-pressure, high-temperature behaviour of cerium up to ∼22 GPa and 820 K using angle-dispersive x-ray diffraction and external resistive heating. Studies above 820 K were prevented by chemical reactions between the samples and the diamond anvils of the pressure cells. We unambiguously measure the stability region of the orthorhombic oC4 phase and find it reaches its apex at 7.1 GPa and 650 K. We locate the α-cF4–oC4–tI2 triple point at 6.1 GPa and 640 K, 1 GPa below t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…As said, the diffraction profiles we observed from the post-oC4 phase were simpler than those from the oC4 phase itself, suggesting they came from a structure with higher symmetry and/or with a smaller unit cell. Previous studies of the high-pressure behavior of Ce have reported similar simplifications of the diffraction profiles at the oC4 → tI2 transition [16,18,30,31], and comparisons of the diffraction profiles from tI2-Ce [16,31,32] with those observed in Pr above 200 GPa [Figs. 4(d) and 4(e)] showed them to be similar.…”
Section: Resultsmentioning
confidence: 55%
“…As said, the diffraction profiles we observed from the post-oC4 phase were simpler than those from the oC4 phase itself, suggesting they came from a structure with higher symmetry and/or with a smaller unit cell. Previous studies of the high-pressure behavior of Ce have reported similar simplifications of the diffraction profiles at the oC4 → tI2 transition [16,18,30,31], and comparisons of the diffraction profiles from tI2-Ce [16,31,32] with those observed in Pr above 200 GPa [Figs. 4(d) and 4(e)] showed them to be similar.…”
Section: Resultsmentioning
confidence: 55%
“…with Θ as the Debye temperature. Using relation for entropy change (11) and knowing that Δv ¼ v 0 À v is volume change and ΔT ¼ T À T 0 , temperature change at phase transition relation (13) will be transformed into…”
Section: S Ponomarova Y Koval Institute For Metal Physicsmentioning
confidence: 99%
“…Detailed reviews of theoretical models, previous experiments and simulations can be found in Refs. [1,24,25].…”
Section: Introductionmentioning
confidence: 99%